Pembangunan model pemindahan pengetahuan tersirat untuk pengurusan lean dalam organisasi - Roshidah, Mohamed (2017)
The increase in competition worldwide had driven organizations, including manufacturing industry in Malaysia to perform the implementation of lean management system in their organizations. Although many studies have been done on the implementation of lean management system, there are few studies done on the development of lean tacit knowledge transfer within the organization to address the challenges in the rapid business environment. This study had identified the key elements to develop the lean knowledge and then investigated the transfer of lean tacit knowledge which involves the sender and the recipient of lean knowledge within the organization. Besides, this study also developed a model of tacit lean knowledge transfer to help organizations develop lean knowledge in their organization. Data was collected through qualitative methods using a single case study in an automotive manufacturing plant in Malaysia. The obtained data was analyzed according to the appropriate theme and code using ATLAS-ti software. The results found that the development of lean knowledge by the sender through various key elements such as lean training, case studies, simulation method, industrial visits and sharing of databases and internet resources (video). The study also found that the transfer of lean tacit knowledge to receiver was delivered through two types of training involving direct and indirect lean training. From the study conducted, a transfer of lean tacit knowledge development model was developed to improve the work performance during the implementation of lean management system in operation. The implementation of lean management will be more effective if every organization had a good lean knowledge and understand how to properly implement lean in the production process